(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to investigate the role of Information Technology Governance (ITG) according to the COBIT5 framework with its five dimensions (direction, evaluation and monitoring, alignment, planning and organization, build, acquisition and implementation, delivery, service and support, monitoring, evaluation, and assessment) in reducing corruption of digital assets. The study community represented a sample of accounting and internal audit department employees in banks operating in Karbala Governorate. The questionnaire was used to measure the relationship between the variables, and 196 forms were distributed. The research concluded that the banks of this study pay great attention to providing a suitable environment that is compatible with innovative methods of Information Technology (IT) and work to acquire and acquire the latest digital innovations in technical fields to enhance their ability to compete and provide banking operations, in addition to finding that ITG is an integral part of banking governance of information in general, and works to provide the best foundations and standards for its application to protect its digital systems and electronic operations. The build, acquisition, and implementation (BAI) has obtained the highest results among other COBIT5 fields, as it directly impacted the corruption of digital assets and prevented and reduced all internal and external risks and operations and hacking to which banking systems are exposed.